Discipline Culture Shapes Students' Religious Character in Islamic Schools: Budaya Disiplin Membentuk Karakter Religius Siswa di Sekolah Islam - Harfi, Ni'mah Fikriyah; Romelah, Romelah; Mardiana, Dina (Universitas Muhammadiyah Sidoarjo, 2025)
School culture is an important element in the education system with the aim of shaping the religious character of students, which is discipline. This study focus to analyze the discipline culture in shaping the religious character of students at the Senior High School level. This research use qualitative approach with case study method, located at Ibnu Sina Integrated Islamic High School in Nunukan, North Kalimantan. The subjects included the principal, vice principal of Curriculum and Student Affairs, two Islamic Religious Education and Ethics teachers, one grade XI homeroom teacher, and three grade XI students (one male, two female). Data collection techniques used observation, unstructured interviews, and documentation. Data validity using source triangulation. Data analysis using the theory of Miles, Huberman, and Saldana with the stages of data condensation, data presentation, and conclusions. The results is that discipline culture is highly emphasized at SMA IT Ibnu Sina through written rules, advice, and sanctions in the event of violation. The discipline culture applied has a major effect on students' religious character, proven by the anxiety in students when they leave prayer or are late in worship. The culture of discipline applied at SMA IT Ibnu Sina has fulfilled the elements of the three dimensions of discipline, namely the prevention dimension, the action dimension, and the resolution dimension. Highlights: Discipline Culture Impact – A structured discipline culture significantly shapes students' religious character. Three-Dimensional Discipline – The school applies prevention, action, and resolution dimensions to enforce discipline. Role of Educators & Parents – Teachers, staff, and parents collaboratively instill discipline and religious values. Keywords: School Culture, Discipline Culture, Religious Character, Character Education